What does overclaiming represent? Well, it depends! - Dunlop, Patrick; Bourdage, Joshua S; de Vries, Reinout E; McNeill, Ilona M; Jorritsma, Karina; Orchard, Megan; Austen, Tomas; Baines, Teesha; Choe, Weng-Khong (2019)
Overclaiming behaviour, as measured by overclaiming questionnaires (OCQs), has been proposed as a potential indicator of unconscious self-enhancement, conscious/deliberate impression management, careless responding, and even genuine subject matter knowledge. However, the evidence for each of these propositions is very mixed. In this research, we draw from the principles of classical expectancy (VIE) theory to show that overclaiming behaviour likely represents different phenomena as a function of the conditions under which it is observed. Specifically, using a ‘personnel selection’ paradigm, we show through multiple studies that overclaiming performs well as an indicator of deliberate faking, provided three conditions are met: (a) faking is associated with a desired goal (valence is high), (b) the OCQ’s content is tailored appropriately to the assessment situation, such that overclaiming becomes instrumental to achieving that desired goal, and (c) respondents’ expectancies regarding their capacity to overclaim successfully are not undermined.